Penatalaksanaan Fisoterapi pada Kasus Motor Delay di Klinik Asya Center Jombang : Studi Kasus - Desinta Tria Ningrum; Atika Yulianti; Putri Sukma Rahayu (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Delayed development is a condition when there is a delay in the child's growth and development process in one or more areas compared to children of the same age. Delayed development in the motor aspect is a significant lag in physical, including physical activities in daily life such as crawling, sitting, standing and walking in children when compared to normal children of the same age. To determine the effectiveness of a combination of interventions such as Expression Head Massage, Myofacial Release, Complete Neurosenso, General Massage, Patterning, Balance Exercise, and Approximation. The evaluation results showed an increase in gross motor skills in children. A 21-month-old child was diagnosed with Motor Delay when first treated, the child could not walk a few steps and standing had to have a handhold, after undergoing routine physiotherapy 3 times a week, now the child can walk a few steps without a handhold.